2012
DOI: 10.5114/pwki.2012.30398
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Ramadan fasting on circadian variation of Turkish patients with acute myocardial infarction

Abstract: A b s t r a c tIntroduction: The mechanisms of circadian variation in cardiovascular events are not clear. Aim: Evaluation of the effect of Ramadan fasting on circadian variation of acute ST-elevation myocardial infarction (STEMI) in Turkish patients.Material and methods: This comparative cross-sectional study included 151 consecutive patients with acute STEMI. The time of onset of STEMI was determined by the attending physician on the basis of patients' self-reports. The patients were divided into two group b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Table 2 shows the five studies, which reported the incidence of MI during Ramadan and other months, as well as the fasting status. Almansori and Cherif,[ 13 ] Turker et al,[ 14 ] and Al Suwaidi et al[ 11 ] studied the effect of the fasting status on the risk of MI hospitalization. Al Suwaidi et al studying 1019 consecutive acute coronary disease patients admitted to a general hospital in the span of 9 months (including a Ramadan month) reported a higher relative risk for MI in the nonfasting group.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 2 shows the five studies, which reported the incidence of MI during Ramadan and other months, as well as the fasting status. Almansori and Cherif,[ 13 ] Turker et al,[ 14 ] and Al Suwaidi et al[ 11 ] studied the effect of the fasting status on the risk of MI hospitalization. Al Suwaidi et al studying 1019 consecutive acute coronary disease patients admitted to a general hospital in the span of 9 months (including a Ramadan month) reported a higher relative risk for MI in the nonfasting group.…”
Section: Resultsmentioning
confidence: 99%
“…[ 13 ] In their study of 151 consecutive Turkish patients with ST-elevation MI (STEMI) during the Ramadan months of 2010 and 2011, Turker et al reported that higher proportions of the STEMI occurred during the nonfasting state. [ 14 ] Baseline hemodynamics (heart rate, systolic-diastolic blood pressure, etc.) and biomedical profiles (hemoglobin, creatinine, total cholesterol, etc.)…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations